Cardiovascular risk factors and frailty in a cross-sectional study of older people: implications for prevention. - O'Halloran, Aisling; Kenny, Rose (My University, 2018)
Objective: to examine the associations of cardiovascular disease (CVD) and cardiovascular risk factors with frailty. Design: a cross-sectional study. Setting: the Irish Longitudinal Study on Ageing (TILDA). Participants: frailty measures were obtained on 5,618 participants and a subset of 4,330 participants with no prior history of CVD. Exposures for observational study: cardiovascular risk factors were combined in three composite CVD risk scores (Systematic Coronary Risk Evaluation [SCORE], Ideal Cardiovascular Health [ICH] and Cardiovascular Health Metrics [CHM]). Main outcome measures: a frailty index (40-items) was used to screen for frailty. Methods: the associations of CVD risk factors with frailty were examined using logistic regression. Results: overall, 16.4% of participants had frailty (7.6% at 50–59 years to 42.5% at 80+ years), and the prevalence was higher in those with versus those without prior CVD (43.0% vs. 10.7%). Among those without prior CVD, mean levels of CVD risk factors were closely correlated with higher frailty index scores. Combined CVD risk factors, assessed using SCORE, were linearly and positively associated with frailty. Compared to low-to-moderate SCOREs, the odds ratio (OR)(95% confidence interval, CI) of frailty for those with very high risk was 3.18 (2.38–4.25). Conversely, ICH was linearly and inversely associated with frailty, with an OR for optimal health of 0.29 (0.21–0.40) compared with inadequate health. Conclusions: the concordant positive associations of SCORE and inverse associations of ICH and CHM with frailty high-light the potential importance of optimum levels of CVD risk factors for prevention of disability in frail older people.
PUBLISHED
Keywords: Cardiovascular risk factors; Frailty; Prevention; Older people; Ageing